Influence of Marsilea crenata and Alpinia purpurata Ethanol Extract on MDA and SOD Testicular Cells of Hyperglycemia Mice - Damayanti, Febriane Eka; Rahayu, Sri; Widyarti, Sri (Graduate School, Universitas Brawijaya, 2023)
Hyperglycemia can induce testicular damage that leads to male infertility. Herbal plants, such as Marsilea crenata and Alpinia purpurata, are used for antioxidant defense systems to repair reproductive disorders due to hyperglycemia. This study aims to evaluate the effect of M. crenata and A. purpurata ethanol extracts on MDA and SOD testes of hyperglycemia mice. This study used a completely randomized design with seven treatment groups (n=4), namely N (control group), H (hyperglycemia mice), Met (hyperglycemia mice given metformin), D1 (0. 09 mg.g-1 M. crenata), D2 (0.2 mg.g-1 A. purpurata), D3 (0.09 mg.g-1 M. crenata + 0.2 mg.g-1 A. purpurata), and D4 (0.09 mg.g-1 M. crenata + 0.4 mg.g-1 A. purpurata). The extracts were administered orally for 17 days. Analysis of testicular MDA and SOD levels was performed by flow cytometry. Data analysis was performed with a one-way ANOVA test and continued with the Tukey test. The results showed that the D4 treatment group, compared to D3, D2, D1, Met, H, and N, showed a better decrease in MDA levels (4.47%) and an increase in SOD levels in the D4 group (4.77%). The research concludes that the combination of 0.09 mg.g-1 M. crenata and 0.4 mg.g-1 A. purpurata was an optimal dose to decrease MDA levels and increase SOD levels in the testes of hyperglycemic mice. Keywords: Alpinia purpurata, Marsilea crenata, MDA, SOD, testes.